Comparing the Sustainable Development Potential of Industries: A Role for Sustainability Disclosures? - Du Plessis, Johan; Bam, Wouter (Sustainability, 2018)
Governments often seek to facilitate sustainable growth through the targeted support of specific industries that are deemed to have considerable sustainable development potential. However, the selection of appropriate sectors generally relies on resource-intensive assessment processes. With the recent flood of sustainability information into the public domain, there appears to exist an opportunity to use this information to improve the efficiency of the initial stages of evaluating target industries. This work investigated the development of a framework that makes use of public sustainability disclosures to rapidly compare industries in terms of their sustainable development potential. The goal was to evaluate whether such a framework could usefully provide a way to prioritize the execution of more in-depth feasibility studies on industries showing superior sustainable development potential. The developed framework was based on the Global Reporting Initiative’s G4 Sustainability Reporting Guidelines and makes use of 18 indicators to compare industries in terms of various triple bottom line considerations. The framework was applied to a case study of the platinum industry in South Africa to establish its usefulness, potential and limitations. The framework facilitated a reasonably holistic, transparent and easily interpretable comparison of industries. However, its consideration of industry fit in the local economy, expected development trends and quantification of indirect economic impacts were found to be areas that could be improved. Some of these concerns might be overcome by the improved availability of public information in the future.